Harmonization of religious life in the community of Pegagan Julu IX Batangari Village, Jumagrat Hamlet, Sumbul Subdistrict, Dairi Regency in the experience of AFI A Stambuk 23 in community service activities - Hasnah Nasution; Heru Syahputra; Lulu Andriani Siregar; Najla Adelia; Putri Yasmin Br Gultom (Privietlab, 2026)
Interfaith harmony is a key pillar in maintaining social stability in Indonesia's diverse society. The village of Pegagan Julu IX, Batangari, Jumagrat Hamlet, Sumbul Subdistrict, Dairi Regency, is a concrete example of local-based harmony practices, but the challenge of a lack of tolerance education among the younger generation is still evident. This study aims to describe the experiences of students majoring in Islamic Theology and Philosophy (AFI A) Stambuk 23 at the State Islamic University of North Sumatra in building harmony and identifying forms of harmony, challenges, and contributions of students during community service. Qualitative research methods with data collection techniques of observation and group discussions were conducted from July 7 to 18, 2025. It can be concluded that religious harmony in the village is achieved through interfaith cooperation in social activities, reinforced by the local wisdom of Batak Pakpak Sangkep Nggelh as the primary binding force. This proves that religious differences can be a strength for sustainable unity.